Correction: Enani et al. The Association Between Dyslipidemia, Dietary Habits and Other Lifestyle Indicators Among Non-Diabetic Attendees of Primary Health Care Centers in Jeddah, Saudi Arabia. Nutrients 2020, 12, 2441 - Sumia Enani; Suhad Bahijri; Manal Malibary; Hanan Jambi; Basmah Eldakhakhny; Jawaher Al-Ahmadi; Rajaa Al Raddadi; Ghada Ajabnoor; Anwar Boraie; Jaakko Tuomilehto (Nutrients, 2026)
The authors wish to make the following corrections to the published article [...]